Identifikasi Penerapan Family Numbering System di Puskesmas Wilayah Dinas Kesehatan Kota Surakarta - Harjanti Harjanti; Astri Sri Wariyanti (Jurnal Rekam Medis dan Informasi Kesehatan, 2019)
Implementation of numbering in the Health District of Dinas Kesehatan Kota Surakarta 1 applies Personal Numbering and 16 health centers implement Family Numbering. The number classification used is 8 digits consisting of 2 initial digits as a regional code, 4 digits as the serial number of the head of the family, 2 digits of the final digit status in the family. However, in the implementation of area code numbering, it has not yet been utilized for the index, but it has not been used for mapping the spread of disease, even if it is used, it helps in making decisions in reducing morbidity. The qualitative analysis research method is a case study approach. Samples of 16 puskesmas with purposive sampling technique. Data collection is done by observation, interview, documentation study and Focus Group Discussion (FGD). The results of the numbering research in the Surakarta City Health Department Area Health Center consists of 8 and 10 digits. Classification of 2 digits area / village / kelurahan code, 4-6 digits sequence number of head of family, final 2 digits of family status code / sequence of visits in one family. The difference in the middle number is due to the different number of patient visits. Utilization of number classification is used to facilitate storage, the percentage of visits, mapping the spread of disease. Policy should be made regarding the implementation of numbering in accordance with the agreement, namely numbering the Unit Numbering Sytem or Family Numbering with personal indexes and the use of 2 digit front numbers and 2 digit final numbers as needed. A tracer is needed to reduce misfolders with data on medical record numbers, patient names, loan dates and borrowing units.